Abdominal Aortic Aneurysm Volumetric Evaluation During Mid-term Follow-Up After Endovascular Sealing Using the Nellix™ Device - El Batti, Salma (2018)
Objectives: To analyze the volumetric evolution of abdominal aortic aneurysms after endovascular sealing (EVAS) with the Nellix™ device during follow-up. Methods: Patients who underwent elective EVAS in our institution in 2014 and 2015 were retrospectively reviewed. Preoperative, postoperative and 1-year scans were processed. A custom software was conceived to assess semi-automated measurements of the aneurysm sac and the endograft sizes including volume, maximum diameter, sectional area and perimeter. Thrombus volume, aneurysm length, mean distance between the stents inside the polymer-filled sacs and endograft migration were also estimated. Manual maximum diameters were measured for comparison. Inter and intra-observer variability of the proposed semi-automated method was evaluated. Results: Pre-EVAS, post-EVAS and last follow-up scans of 12 patients were finally analyzed during a mean follow-up of 17 ± 5 months. No endograft migration or endoleak were detected. During follow-up, aneurysm volume and perimeter slightly increased compared to post-EVAS scans (+ 1 and + 5%, respectively, p < 0.05). A systematic 6% enlargement of the endobag volume was also observed (range 1–15 mL, p < 0.001). Endobag maximum diameter, area and perimeter increased 4, 8, and 8%, respectively (all p < 0.01). Mean plane-by-plane distance between stents increased 4% (p < 0.05). Mean thrombus volume did not change during follow-up, although a high variability was observed. Aneurysm and thrombus volume changes were highly correlated (r = 0.93, p < 0.001). No associations were observed between aneurysm and endobag volume changes. Intra- and inter-observer variability was below 1.7 and 2.4% for diameter and volume measurements, respectively. The automated measurements of post-EVAS aneurysm diameter and volume were higher than preoperative (p < 0.05). Maximum diameters measured manually did not differ between scans. Conclusion: Small aneurysm volume enlargement detected during a mid-term follow-up was associated with thrombus size change, whereas systematic endograft expansion resulted independent from the aortic growth. Volumetric measurements using a semi-automated method could quantify small changes in aneurysm, endograft and thrombus sizes not detected by manually defined maximal diameters.